Perceived Luxury Value and Technology Acceptance in TikTok Live Streaming: The Mediating Role of Customer Engagement on Purchase Intention (A Study on Consumers in Java, Indonesia) - safhera, Maya; Sugiarto, Catur (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study examines how perceived luxury value, consisting of financial, functional, individual, and social dimensions, and technology acceptance factors, namely perceived ease of use and perceived usefulness, influence customer engagement and purchase intention in luxury live streaming shopping in Indonesia. Using a quantitative approach with purposive sampling, data from 354 respondents were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through SmartPLS 4. The results indicate that all relationships are significant. Social value has the strongest effect on customer engagement, followed by individual, functional, and financial values. Both perceived usefulness and perceived ease of use significantly affect engagement, with usefulness showing a greater impact. Customer engagement enhances purchase intention and mediates the relationship between perceived luxury value and technology acceptance factors. The model explains 71.3% of the variance in engagement and 66.8% in purchase intention, emphasizing engagement as the key mechanism linking value perceptions and technology acceptance. The study extends the Stimulus–Organism–Response (SOR) framework and Technology Acceptance Model (TAM) to luxury live streaming contexts and provides insights for luxury brands to strengthen competitiveness through interactive experiences, intuitive usability, and persuasive live demonstrations.